Morphometric Analysis of a Tropical Medium River System: A Case from Bharathapuzha River Southern India - P. P. Nikhil Raj and P. A. Azeez (Open Journal of Modern Hydrology, 2012)
Baseline morphometric information at a sub basin level is essential to develop appropriate strategy for sustainable, so- cially acceptable, ecologically benign and economically viable development of a river basin. The present study was carried out in one of the less studied Bharathapuzha river basin (BRB), the second longest river in the state of Kerala, India. The annual discharge of the river is 3.94 km 3 . Nevertheless the basin, which receives about 1828 mm of annual rainfall, in recent years has been facing dearth of water. We used GIS and RS tools to study the morphometric charac- teristics of the basin. The seventh order main river is formed by several lower order streams forming a dentritic flow pattern. Basin geology, slope and rainfall pattern in the basin determine the morphometric characteristics of the basin. The linear aspects of the basin including stream length ratio and bifurcation ratio indicate the role of relief in the basin while the areal ratios indicate the elongate nature of the basin.